Risk factors for refractory patent ductus arteriosus to initial medical treatment in preterm infants - Yazıcı, Aybüke; Kanmaz Kutman, Hayriye Gözde; Kadıoğlu Şimşek, Gülsüm; Siyah Bilgin, Betül; Canpolat, Fuat Emre; Oğuz, Şerife Suna (The European Research Journal, 2025)
Objectives: This study aims to identify risk factors and clinical markers for refractory patent ductus arteriosus to the initial medical treatment and determine appropriate treatment strategies. The goal is to define the newborns who will respond to treatment and to prevent patients from adverse effects of medical or surgical treatment of patent ductus arteriosus. Methods: Preterm infants with hemodynamically significant patent ductus arteriosus and whose gestational age was under 30 weeks were retrospectively evaluated. Infants who responded to the initial medical treatment (paracetamol or ibuprofen) were compared to those non-responders. Neonatal characteristics and comorbidities were compared between the groups. Results: Data from a total of 91 infants were analyzed. The mean gestational age was 27±1.9 weeks vs. 26±1.9 weeks (P=0.10), and birth weight was 1,056±290 vs. 974±318 g (P=0.61), respectively in responder and refractory groups. Success rates for patients treated with paracetamol (n=49) were 57.4%, while for those treated with ibuprofen (n=42), it was 42.6% (P=0.47). Echocardiographic findings such as ductal size 2.48±0.69 vs. 2.55±0.66 mm (P=0.75), and left atrium/aortic root ratio 1.73±0.4 vs. 1.64±0.25, (P=0.14) were also comparable. Incidence of severe intraventricular hemorrhage (22.7% vs 4.3%, P=0.009) and periventricular leukomalacia was significantly higher in the refractory group (53.1% vs. 22.2%, P=0.008). Conclusions: Combining multiple risk factors into a clinical decision-making model or algorithm could enhance the predictive accuracy of treatment response. Moreover, ongoing monitoring and tailored treatment adjustments based on individual responses and side effects are crucial for effectively managing patent ductus arteriosus in preterm infants.